Penerapan Finite State Machine Dalam Inteaksi Dialog Dalam Novel Game Forest Life - Mustofa Mustofa; Vadlya Maarif; Achmad Novel; Sunanto Sunanto; Chandra Kesuma (Computer Science (CO-SCIENCE), 2022)
Human life is increasingly complex in today's technology-filled era, often making people feel tired and tired in their activities. Of course, the presence of this technology also provides an answer by providing an increasingly creative and varied variety of entertainment such as video streaming services, social media, online comics, internet, video games and many other services. Of the several entertainments that are quite popular, video games are one of the entertainments that are consistently the main choice. The game is currently quite in demand and has been favored by various ages, especially teenagers. However, currently the majority of video games circulating in the country come from outside and lack of education. For this reason, the need for literacy in making games that are easy to make but still fun to play and have an educational element. This study tries to create a simple novel game by utilizing a finite state machine to facilitate the design of the storyline. By using the finite state machine, designing video game storylines becomes faster and easier.